United for health to improve urban food environments across five underserved communities: a cross-sector coalition approach - Denise D. Payán; LaVonna B. Lewis; Jacqueline Illum; Breanna Hawkins; David C. Sloane (BMC Public Health, 2022)
Abstract Background Cross-sector coalitions can be a powerful vehicle to promote adoption and implementation of evidence-based programs and policies across diverse racial/ethnic communities with a high chronic disease burden. Few studies have examined coalition composition, function, or capacity to promote learning among members. Methods We used a mixed methods approach to examine the United for Health coalition’s implementation of multiple food environment interventions across five low-income communities of color in Los Angeles, California (USA). At the coalition-level, key measures included the collaborative environment, membership characteristics, process and structure, communication, resources, strengths, challenges/barriers, and community impact. At the organizational- and individual-levels, we collected data on participation, leadership development, intraorganizational change, perceived benefits, and learning outcomes. Findings Overall, the United for Health coalition produced five community gardens, three pop-up produce markets, and one farmers’ market; members also expanded Electronic Benefits Transfer (EBT) access at three existing farmers’ markets. Findings indicate early coalition strengths included having a mutual purpose, which was maintained throughout the study period. Coalition participation and engagement was consistently high, while coalition and inter-organizational communication improved over time. Strengths were membership diversity and the availability of learning opportunities. Benefits included leadership development and strategic alignment across organizations. Members demonstrated an increased awareness of the importance of culturally adapted interventions and knowledge of community health planning topics. Key implementation challenges were a lack of resources and social context barriers. Conclusions Examining coalition function and maturation in a real-world context reveals important lessons for scholars and practitioners committed to addressing nutrition-related health disparities in marginalized and historically underserved communities. Future work should investigate the sustainability of externally funded cross-sector coalitions after funding ceases.